Sufficient harvest-yields despite low soil fertility : The special strategy of Nepalese mountain farmers - Haffner, Willibald; Justus Liebig University Giessen (My University, 1992)
The climatic-ecologically favourable location of the monsoon-tropical Nepal Himalayas finds its reflection in the high population density in the Lower Himalayas, reaching up to 400 inhabitants/km2 and - just like in other developing countries- still growing steadily. Agricultural yields having guaranteed the self-sufficiency of the population with staple food products for centuries are unexpectedly high considering the unfavourable relief and soil conditions so very typical of the Lower Himalayas.If the Lower Himalayas of Nepal give the impression, especially during the rainy season, of a luxuriant green landscape and if yields adequate for the self-sufficiency of a slowly but steadily growing mountain population have been attained for centuries, this is due to the fact that the population is well aware of how to successfully manage its natural environment: Nepalese mountain farmers have developed and handed down to subsequent generations special forms of argrarian technology which considerably reduce, if not eliminat, the given unfavourable ecological soil factors.

Die klimaökologische Gunstlage des Nepal-Himalaya spiegelt sich wider in einer hohen Bevölkerungsdichte, die im Vorderhimalaya bis zu 400 E/km2 erreicht und - wie in anderen Entwicklungsländern- auch heute noch stetig zunimmt. Flächenerträge, welche über Jahrhunderte die Selbstversorgung der Bevölkerung mit Grundnahrungsmitteln sicherstellen konnten, sind trotz der für den Vorderhimalaya typischen ungünstigen Relief- und Bodenbedingungen wider Erwarten hoch.Wenn der Vorderhimalaya Nepal, insbesondere zur monsunalen Regenzeit, den Eindruck einer üppig grünen Agrarlandschaft macht, wenn seit Jahrhunderten ausreichende Erträge zur Selbstversorgung einer zwar langsam, aber stetig anwachsenden Gebirgsbevölkerung erwirtschaftet wurden, dann hat dies seinen Grund darin, dass die Bevölkerung gute Kenntnisse darüber besitzt, wie sie ihre natürliche Umwelt erfolgreich nutzen kann: Nepalesische Gebirgsbauern haben besondere Formen der Agrartechnik entwickelt und tradiert, welche die bodenökologischen Ungunstfaktoren, wenn nicht völlig kompensieren, so doch beträchtlich abschwächen.
Keywords: Nepal; Landwirtschaft; Hochgebirge; Himalaya; Terrassenwirtschaft; Nepal; Agriculture; Erosion; Himalaya; ddc:550